Salivary cytokine biomarker concentrations in relation to obesity and periodontitis - Syrjäläinen, Sanna (My University, 2019)
Systemic low-grade inflammation is associated with obesity. Aim of this study was to examine the association between obesity and salivary biomarkers of periodontitis. Salivary interleukin (IL)-1-receptor antagonist (IL-1Ra), IL-6, IL-8, IL-10, and tumor necrosis factor (TNF)-α concentrations were measured from 287 non-diabetic obese (BMI >35kg/m2) individuals and 293 normal weight (BMI 18.5-25kg/m2) controls. Their periodontal status was defined according to a diagnostic cumulative risk score (CRS) to calculate the risk of having periodontitis (CRS I, low risk; CRS II, medium risk; CRS III, high risk). In the whole population, and especially in smokers, higher IL-8 and lower IL-10 concentrations were detected in the obese group compared to the control group, while in non-smoking participants the obese and control groups did not differ. IL-1Ra and IL-8 concentrations were higher in those with medium or high risk (CRS II and CRS III, p < 0.001) of periodontitis, whereas IL-10 and TNF-α concentrations were lower when compared to those with the low risk (CRS I). In multivariate models adjusted for periodontal status, obesity did not associate with any salivary cytokine concentration. In conclusion, salivary cytokine biomarkers are not independently associated with obesity while their concentration is dependent on periodontal status.
Keywords: lihavuus, parodontiitti, sytokiini, tulehdus, sylki